2022
DOI: 10.5194/angeo-40-619-2022
|View full text |Cite
|
Sign up to set email alerts
|

Multi-instrument observations of polar cap patches and traveling ionospheric disturbances generated by solar wind Alfvén waves coupling to the dayside magnetosphere

Abstract: Abstract. During minor to moderate geomagnetic storms, caused by corotating interaction regions (CIRs) at the leading edge of high-speed streams (HSSs), solar wind Alfvén waves modulated the magnetic reconnection at the dayside magnetopause. The Resolute Bay Incoherent Scatter Radars (RISR-C and RISR-N), measuring plasma parameters in the cusp and polar cap, observed ionospheric signatures of flux transfer events (FTEs) that resulted in the formation of polar cap patches. The patches were observed as they move… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 89 publications
0
0
0
Order By: Relevance
“…In Section 3.2, we present observations of TIDs generated by solar wind-M-I-T coupling on the dayside following the arrival of high-speed streams (HSSs) permeated by solar wind Alfvén waves (Belcher and Davis, 1971;Tsurutani et al, 1987). Solar wind Alfvén waves can modulate ionospheric convection and currents producing polar cap density patches and TIDs (Prikryl et al, 1999(Prikryl et al, , 2005(Prikryl et al, , 2022.…”
Section: Agwsmentioning
confidence: 99%
See 4 more Smart Citations
“…In Section 3.2, we present observations of TIDs generated by solar wind-M-I-T coupling on the dayside following the arrival of high-speed streams (HSSs) permeated by solar wind Alfvén waves (Belcher and Davis, 1971;Tsurutani et al, 1987). Solar wind Alfvén waves can modulate ionospheric convection and currents producing polar cap density patches and TIDs (Prikryl et al, 1999(Prikryl et al, , 2005(Prikryl et al, , 2022.…”
Section: Agwsmentioning
confidence: 99%
“…The Worldwide Atmospheric Gravity-wave Studies (WAGS) program (Crowley and Williams, 1988;Williams et al, 1993) showed that large-scale TIDs originate in auroral latitudes. TIDs generated by AGWs originating in the lower atmosphere come from a variety of sources, including tropospheric weather systems (Bertin, Testud and Kersley, 1975;Bertin et al, 1978;Waldock and Jones, 1987;Oliver et al, 1997;Nishioka et al, 2013;Azeem et al, 2015), total solar eclipses (Zhang et al, 2017;Mrak et al, 2018), the polar vortex (Frissell et al, 2016), volcanic eruptions, earthquakes, and tsunamis (Yu, Wang and Hickey, 2017;Nishitani et al, 2019;Themens et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations